Penyusunan Standard Operating Procedure (SOP) Produksi Inovasi Ecobrick - Hayati Mukti Asih; Syifa Fitriani (Jurnal Ilmiah Teknik Industri, 2018)
Increasing plastic waste in Indonesia make residents around Brontokusuman Waste Bank RW 20-22 Yogyakarta produce ecobrick.  Ecobrick is one way of handling plastic waste by packing clean and dry plastic into a plastic bottle to specified density.  The problem nowadays is nostandard operating procedure (SOP) for the ecobrick production.  Therefore, this study aims to develop SOP for ecobrick production to be systematic and structured so as to maintain product quality and consistency both in terms of aesthetics and product weight.  This research was conducted using qualitative methods, like observation, interviews with actors and SOP experts, and documentation.  Then, data analysis method by Miles and Huberman was carried out, such as reduction, evaluation and conclusion.  This research also presents preparation of initial SOP design, simulation of initial SOP production and problem identification, then improvement, final SOP design and simulation.  The result is SOP production of standardized aesthetic and weightecobrick.